Nanosized caltrops enable selective capture and directional maneuvering of water droplets - Haoting Cai; Wei Tong; Lichuan Wei; Mengjie Song; Yugang Zhao; Kang Li; Hua Zhang; Chun Yang; Ping Cheng (Communications Materials)
Abstract Surface design by tailoring topographical features and interface function groups to modulate dynamic or kinetic behaviors of liquid droplets, has been an increasing hotspot due to its broad spectrum of applications in biochemical diagnosis, microfabrication, and energy conversion systems. Here we report an engineered surface decorated by packed nanosized caltrops resulting from two perfectly articulated oxidation processes, where self-assembled nanoislands generated in the 1st plasma oxidation serve as protective masks in the 2nd chemical oxidation. As caltrops per design can effectively block lateral motion, the present surface can anchor contact lines of advancing water films when being hydrophilic and selectively capture impinging droplets when being hydrophobic. Furthermore, biphilic patterns can be readily obtained by integrating nanocaltrops with other surface asperities, engendering directional droplet maneuvering and designated droplet arraying. This work provides guidelines in designing nanostructures that achieve on-demand manipulation of droplets and flow patterns for multifunctional applications.